The Psychometric Properties of the Norwegian version of Marschak Interaction Method (MIM) - Rye, Marte; Drozd, Filip (PsykTestBarn, 2021)
Description: Marschak Interaction Method (MIM) is an observation method developed to assess caregiver-child interactions. MIM was developed by Marianne Marschak in 1960 and later adapted to be used together with the intervention Theraplay. The method is copyright protected by The Theraplay Institute. MIM consists of sets of tasks the caregiver and the child perform together. The tasks reflect the four Theraplay dimensions: Structure, Engagement, Nurture, and Challenge. Different rating systems have been developed, for instance the Marschak Interaction Method Rating System (MIMRS), Dyadic Emotional Interaction Style (D-EIS) and MIM-Psychometrics (MIM-P). Literature search: The literature search identified two articles which used two different rating systems. Both were cross-sectional studies performed in Denmark with a limited sample size. One article involved refugee families with children under 18 years of age (N = 21), who were referred to treatment for family violence, while the second involved parents with children between 4 and 12 years old (N = 36) who were referred to treatment due to family related difficulties. Psychometrics: Both articles reported inter-rater reliability and included estimations of construct validity. Neither article reported internal consistency nor other types of validity. Conclusion: The psychometric properties of the observation method MIM has not been assessed in Scandinavian countries. The existence of several rating systems complicates an overall evaluation of the validity and reliability for the MIM. For all rating systems, there is a need for more research on its psychometric properties with adequate sample sizes.